GYÖRGY LIGETI’S SECOND STRING QUARTET: BIOGRAPHICAL INFLUENCES AND NEW TECHNIQUES - Tudor FERARU (Studia Universitatis Babeş-Bolyai. Musica)
Despite György Ligeti’s personal denial of the direct influences on his music by the events from his young years, the listener can easily find traces and echoes of traumatizing experiences in many of his compositions. The study attempts to answer the following question: to what extent is Ligeti’s music tributary to the composer’s unfortunate youth?